2017
DOI: 10.1186/s12903-017-0378-1
|View full text |Cite
|
Sign up to set email alerts
|

The microbial changes in subgingival plaques of orthodontic patients: a systematic review and meta-analysis of clinical trials

Abstract: BackgroundOrthodontic treatment was found to have an impact on the quantity and constitution of subgingival microbiota. However, contradictory findings regarding the effects of fixed appliances on microbial changes were reported. The aim of this systematic review was to investigate the microbial changes in subgingival plaques of orthodontic patients.MethodsThe PubMed, Cochrane Library, and EMBASE databases were searched up to November 20, 2016. Longitudinal studies observing microbial changes in subgingival pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 25 publications
3
54
2
3
Order By: Relevance
“…Many research studies have been carried out on microbial changes during fixed appliance treatment ( Freitas et al, 2014 ; Ireland et al, 2014 ). Our previous research found that the level of subgingival periodontal pathogens could temporarily increase after the placement of a fixed appliance ( Guo et al, 2017 ). However, we know little about how clear aligner treatment impacts microbiota and periodontal health.…”
Section: Discussionmentioning
confidence: 99%
“…Many research studies have been carried out on microbial changes during fixed appliance treatment ( Freitas et al, 2014 ; Ireland et al, 2014 ). Our previous research found that the level of subgingival periodontal pathogens could temporarily increase after the placement of a fixed appliance ( Guo et al, 2017 ). However, we know little about how clear aligner treatment impacts microbiota and periodontal health.…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontic treatment has been associated with certain adverse effects to the periodontium, which are generally thought to be transient and not related to any lasting tissue damage . These include increased clinical plaque/bleeding indices, enlargement of gingival pockets, marginal bone loss and quantitative or qualitative changes in the oral microbiota . Orthodontic treatment‐induced microbial changes can be attributed to the plaque‐retentive characteristics of orthodontic appliances, while deepening of the gingival crevice through hyperplasia might offer a favourable environment for periodonto‐pathogenic anaerobic bacteria …”
Section: Introductionmentioning
confidence: 99%
“…The only existing systematic review of treatment‐induced subgingival changes assessed a limited number of databases, while methodological issues, such as choice of a statistical model for data synthesis, lack of subgroup analyses for potentially modifying factors, and grading of clinical recommendations with the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach justified this study.…”
Section: Introductionmentioning
confidence: 99%
“…Indirectly, it also addresses the health of supporting structures [10]. A recent systematic review analyzed 13 studies; it concluded that the levels of subgingival periodontal pathogens increased after orthodontic appliance placement and appeared to return to the pretreatment levels several months later [11]. Placement of orthodontic brackets influences the accumulation and composition of the supragingival and subgingival microbiota [12].…”
Section: Discussionmentioning
confidence: 99%